FREQUENCY OF STRESS AMONG PILOTS OF A BASE: Stress Among Pilots - Iqbal, Mahmood; Zaman, Muhammad (Pakistan Armed Forces Medical Journal, 2015)
Objective: To determine the frequency level of stress among the pilots stationed at a base in Pakistan. Study Design: Cross-sectional descriptive study. Place and Duration of Study: Study was carried out at an air base of Pakistan from April to July 2013. Material and Methods: All aviators on active flying duties with no past psychiatric history were included in this study. After taking consent and permission from authorities each pilot was given two self-reporting forms consisting of life inventory composed of thirty items depicting recent life changes. Life events included in this scale ranged from highest score of 100 for death of spouse to minimum score of 11 for minor violations of law. The stress questionnaire included a symptoms list with five possible responses of never, seldom, sometimes, often and regular. Pilots were to choose most appropriate response that fitted best for the last six months. This questionnaire consisted of 75 items. Items covered almost all physical, psychological and cognitive symptoms that might occur in stress. Results: A total of 74 aviators participated in this study. On stress inventory 31 (42%) pilots had no significant problems in their lives, 22 (30%) had mild stress, and 17 (23%) pilots had moderate stress while only 4 (5%) pilots exhibited to have major stress. Results of stress questionnaire reveal that 35% of pilots had below average stress level, 27% pilots had above average stress levels, 23% of the pilots showed average person’s stress level, and 9.45% of the pilots that is only 7 out of 74 exhibited high stress level. Conclusion: Majority of Pakistani pilots have reported low level of stress.